Governança de TIC: um Panorama da Adoção de Melhores Práticas em Empresas do Estado de Sergipe - da Silva, Claudio J. N.; Ribeiro, Quelita A. D. S.; Soares, Michel S.; do Nascimento, Rogério P. C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Information and Communication Technologies (ICT) have become fundamental in the organizational process. In order to align ICT objectives with business objectives, many organizations make use of governance practices that not only help in the management of ICT, but also allow for transparency and control over spending, investment and objectives. This study aims to identify, through the application of a survey, the use of the best practices of ICT governance in the scope of companies of the State of Sergipe. It also seeks to understand how is the strategic planning and alignment between ICT and business in these companies.